Effectiveness of probiotics, prebiotics, and prebiotic‐like components in common functional foods. Issue 4 (26th May 2020) - Peng, Mengfei; Tabashsum, Zajeba; Anderson, Mary; Truong, Andy; Houser, Ashley K.; Padilla, Joselyn; Akmel, Ahlam; Bhatti, Jacob; Rahaman, Shaik O.; Biswas, Debabrata
Abstract: The bioactive ingredients in commonly consumed foods include, but are not limited to, prebiotics, prebiotic‐like components, probiotics, and postbiotics. The bioactive ingredients in functional foods have also been associated with beneficial effects on human health. For example, they aid in shaping of gut microflora and promotion of immunity. These functional components also contribute in preventing serious diseases such as cardiovascular malfunction and tumorigenesis. However, the specific mechanisms of these positive influences on human health are still under investigation. In this review, we aim to emphasize the major contents of probiotics, prebiotics, and prebiotic‐like components commonly found in consumable functional foods, and we present an overview of direct and indirect benefits they provide on human health. The major contributors are certain families of metabolites, specifically short‐chain fatty acids and polyunsaturated fatty acids produced by probiotics, and prebiotics, or prebiotic‐like components such as flavonoids, polyphenols, and vitamins that are found in functional foods. These functional ingredients in foods influence the gut microbiota by stimulating the growth of beneficial microbes and the production of beneficial metabolites that, in turn, have direct benefits to the host, while also providing protection from pathogens and maintaining a balanced gut ecosystem. The complex interactions that arise among functional food ingredients, human physiology, the gut microbiota, and their respective metabolic pathways have been found to minimize several factors that contribute to the incidence of chronic disease, such as inflammation oxidative stress.